2006
DOI: 10.1097/01.opx.0000195569.36185.fd
|View full text |Cite
|
Sign up to set email alerts
|

Tear Breakup Dynamics: A Technique for Quantifying Tear Film Instability

Abstract: These methods allow objective quantification and tracking of the phenomenon of tear breakup. Our results suggest that tear breakup stresses the corneal surface, resulting in stimulation of underlying nociceptors. The tear film of dry eye subjects was less stable than controls. They had a larger AB measured from the last video frame before MBI (i.e., just before blinking) than did controls. This perhaps reflects adaptation to the repeated stress of tear instability in dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 32 publications
5
58
2
Order By: Relevance
“…The differences between groups reached statistical significance (Mann-Whitney U test, P < 0.05) for ''irritation'' and ''pricking.'' These results agree with our previous studies, which indicate that TBU in eye opening trials was associated with irritation, stinging, and burning, 15,20,22 but also suggest that diminishing corneal fluorescence over time without TBU is associated with an irritative affective response. The difference in discomfort experienced by subjects in the BU and BUmin groups is illustrated in Figures 2 and 3, which show individual data for the change in discomfort during trials reported by four of the subjects in this study.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The differences between groups reached statistical significance (Mann-Whitney U test, P < 0.05) for ''irritation'' and ''pricking.'' These results agree with our previous studies, which indicate that TBU in eye opening trials was associated with irritation, stinging, and burning, 15,20,22 but also suggest that diminishing corneal fluorescence over time without TBU is associated with an irritative affective response. The difference in discomfort experienced by subjects in the BU and BUmin groups is illustrated in Figures 2 and 3, which show individual data for the change in discomfort during trials reported by four of the subjects in this study.…”
Section: Resultssupporting
confidence: 83%
“…23 Subjects were then seated behind a slit lamp biomicroscope fitted with a digital video camera, and 2 lL of sodium fluorescein (2%) was pipetted into the tested eye while the other eye was patched shut. As in previous studies, subjects were asked to keep the tested eye open as long as possible 20,21 while they turned a knob (potentiometer) to indicate the level of discomfort in the tested eye on a 0 to 10 scale (0 ¼ no discomfort and 10 ¼ very uncomfortable). 22 Following each trial, subjects rated their overall discomfort on separate integer scale of 1 (no discomfort) to 10 (very uncomfortable) and then indicated the level of irritation, stinging, burning, pricking, and cooling on visual analogue scales (VAS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown fluorescein tear break up time (FBUT) to be different between dry eye and normal patients, 1-3 and it is often used within clinical research to monitor the effectiveness of treatments. 4-6 However, this measure has been shown to have modest repeatability at best when the same examiner performs the test.…”
mentioning
confidence: 99%